2018
DOI: 10.1371/journal.pone.0191915
|View full text |Cite
|
Sign up to set email alerts
|

Circulating, cell-free DNA as a marker for exercise load in intermittent sports

Abstract: BackgroundAttempts to establish a biomarker reflecting individual player load in intermittent sports such as football have failed so far. Increases in circulating DNA (cfDNA) have been demonstrated in various endurance sports settings. While it has been proposed that cfDNA could be a suitable marker for player load in intermittent sports, the effects on cfDNA of repeated sprinting as an essential feature in intermittent sports are unknown. For the first time, we assessed both alterations of cfDNA due to repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…The low level of DNA release into the circulation seen in good health becomes elevated in response to induced cellular injury in various pathologic states including sepsis and severe infections, trauma, ischemic injury, autoimmune disease, and cancer [54][55][56][57][58][59]. Transient non-pathologic cfDNA elevations also occur after intense or prolonged exercise [60], but rapidly return to baseline upon recovery, consistent with the short half-life of cfDNA fragments in plasma, which generally ranges from 4-30 min [61][62][63]. Despite complexity of cfDNA origins in mammalian biology and need for consideration of contributing clinical conditions, the preponderant generation of donor-specific and recipient-specific cfDNA from cellular apoptosis in transplant patients and its relatively short plasma half-life make cfDNA DF an elegant and dependable temporal indicator of ongoing selective injury to the donor organ.…”
Section: Introductionmentioning
confidence: 99%
“…The low level of DNA release into the circulation seen in good health becomes elevated in response to induced cellular injury in various pathologic states including sepsis and severe infections, trauma, ischemic injury, autoimmune disease, and cancer [54][55][56][57][58][59]. Transient non-pathologic cfDNA elevations also occur after intense or prolonged exercise [60], but rapidly return to baseline upon recovery, consistent with the short half-life of cfDNA fragments in plasma, which generally ranges from 4-30 min [61][62][63]. Despite complexity of cfDNA origins in mammalian biology and need for consideration of contributing clinical conditions, the preponderant generation of donor-specific and recipient-specific cfDNA from cellular apoptosis in transplant patients and its relatively short plasma half-life make cfDNA DF an elegant and dependable temporal indicator of ongoing selective injury to the donor organ.…”
Section: Introductionmentioning
confidence: 99%
“…Due to limiting sample volume, we were not able to measure the starting concentration of cfDNA purified from fingerstick plasma, but other studies have demonstrated capillary cfDNA concentrations to be ~50% lower than venous levels on average (i.e. approximately 10 ng/mL or 10 pg/μL) 31 , 32 . However, there is growing evidence that substantial venous cfDNA losses occur during silica membrane-based purification (unlike precipitation-based methods) 33 – 35 , which may account for the observed trend in WG-RCA yields (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, we assume that our cortisol dataset based on the measurement procedure with three time points (08:30 AM, 10:30 AM, and 12:30 PM) is not entirely comparable with the time points used previously [45]. Some studies have reported that cfDNA levels already increase with moderate PA below the level of the aerobic-anaerobic transition [26,28]. The results of the cfDNA AUCi posterior distributions suggest that such a association is also more likely in both teaching settings.…”
Section: A) B) C) D)mentioning
confidence: 94%
“…In particular, the cfDNA has been proven to be highly sensitive to physical exercise as a stressor (see [27] for review). Reportedly, the cfDNA increased with moderate PA below the level of the aerobic-anaerobic transition [26,28]. Regarding psychological stress, little is known about the reactivity of cfDNA concentrations.…”
Section: Introductionmentioning
confidence: 99%